2018
DOI: 10.30464/jmee.2018.2.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Electric vehicles: Problems or solutions

Abstract: This paper discusses the current directions of vehicle developments, as well as the barriers and opportunities for using electric vehicles instead of conventional vehicles. There is also mentioned a problem of the battery charging system. Compared to refueling gasoline powered vehicles, charging of battery electric vehicles takes considerably more time, which renders a single-purpose charging infrastructure inconvenient. However, an objective of this article is also to investigate the future market prospects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…CO 2 as a component of exhaust gases (but also an indicator of energy conversion processes for fuel combustion in powertrain systems) makes up the qualitative course of the energy conversion process and, additionally, is closely related to the fuel/energy consumption constituting the basis of energy conversion processes. The work of Piatkowski and Puszkiewicz [6] showed that zero emission of vehicles (e.g., CO 2 emissions) may be the result of the balance of production processes and vehicle use or of obtaining the energy to power the vehicles from renewable sources (RES). When solving the emissivity problems and pointing to the feature of electric motors that constitutes their advantage over internal combustion engines, it should be noted that not only the energy element is crucial here, but also aspects important from the user's point of view, such as range or costs.…”
Section: Co 2 As An Indicator Of Road Energy Consumptionmentioning
confidence: 99%
“…CO 2 as a component of exhaust gases (but also an indicator of energy conversion processes for fuel combustion in powertrain systems) makes up the qualitative course of the energy conversion process and, additionally, is closely related to the fuel/energy consumption constituting the basis of energy conversion processes. The work of Piatkowski and Puszkiewicz [6] showed that zero emission of vehicles (e.g., CO 2 emissions) may be the result of the balance of production processes and vehicle use or of obtaining the energy to power the vehicles from renewable sources (RES). When solving the emissivity problems and pointing to the feature of electric motors that constitutes their advantage over internal combustion engines, it should be noted that not only the energy element is crucial here, but also aspects important from the user's point of view, such as range or costs.…”
Section: Co 2 As An Indicator Of Road Energy Consumptionmentioning
confidence: 99%